Determinants of job satisfaction: How satisfied are employees at public universities / Soo Kum Yoke... [et al.] - Soo, Kum Yoke; Zainon, Saunah; Hj Roslim, Norwati; Hasan, Nor Haniza (UiTM Cawangan Johor, 2019)
The success of an organisation depends a lot on its employees’ satisfaction in carrying out their roles and duties. Thus, job satisfaction is seen to be a significant predictor of employees’ work-related well-being. The current paper aims to determine the employees’ role within the organisation in relations to job satisfaction, as well as to determine whether working environment contributes to job satisfaction. The paper also aims to examine the employer- employee relationship in accomplishing job satisfaction. This study was conducted in a branch campus of a public university consisting of 17 lecturers. It uses quantitative method by means of a survey consisting of 18 items that are divided into three parts which include role within the organisation, working environment and relationship with superior. The results were tabulated using descriptive analysis. The findings show for the role of employees in the organisation, there were a small number of employees who did not feel valued by the organisation. This could be contributed by their not gaining permanent status of employment. The findings also showed that a small number of employees found the workplace environment stressful. These employees had less than three years of work experience which could cause them to have problems adapting fully to their work environment. Finally, it was found that the lecturers felt they were treated with respect by their superior and their relationship with their superior was generally good. It is recommended for future research to consider a more comprehensive study involving a larger scale of respondents from public and private universities.